Postać Jana Pawła II w polonijnych podręcznikach do kształcenia literacko-kulturalnego - Pelczar, Wojciech (Zielona Góra: Uniwersytet Zielonogórski)
The article presents one researching problem connected with textbooks, which were edited by the Polish education organisations in The United States of America, Great Brittain and Canada after the second world war. The author is interested in Holy Father John paul II and his place in Polish emigrants schoolbooks. Analisys publications, numeral comparison, qualitatively description permit to find out that person John Paul II is for Polish emigrantsreason to be proud and intensifies connection with Poland.
Keywords: Jan Paweł II, papież (1929-2005); dydaktyka literatury; podręczniki; polonia; Stany Zjednoczone Ameryki Północnej; Wielka Brytania; Kanada